Tissue Engineering Rechtliche Grenzen und Voraussetzungen - Wernscheid, Verena (Universitätsverlag Göttingen, 2012)
Tissue engineering, the creation of human tissue in the laboratory by the use and propagation of human cells to develop commercial products, faces many problems concerning its legal regulation. There have been numerous alterations to the laws governing biotechnology -derived medicinal products. However, difficulties remain regarding their legal classification. This work shall give a legal survey of the whole procedure of tissue engineering concerning German and European law.